Por uma análise psicossocial do curso de direito - Novaes, Adelina de Oliveira (2010)
This work aims at understanding the social representations of Brazil from a group of law students perspective and identifying the role of the Law Major for the shaping of the country s future professionals. We accompanied law students during their first three years at a private law school in the East suburb of São Paulo, and we tried to identify all possible transformations of their representations of Brazil, mainly those provoked by the law school courses. 27 students who attended morning classes and 26 who attended evening classes participated in our research. The first data collection took place in the second semester of 2006, when these students were enrolled in their first law school year. Making use of questionnaires, we asked them to draw the country and its contents, and in the verbal expression questions, we asked them to identify and describe a fact that they believed to be relevant for Brazil. We also asked the students to describe what it felt like to be Brazilian. From the analysis of the drawings and the lexical analysis of the questionnaires´ textual contents, we were able to identify evidence of these students´ social representations of Brazil. Such evidence guided the creation of scripts for subsequent collective reflexive interviews, when the students were then given the chance to ressignificate the data previously collected and discuss current issues related to their representations of Brazil. Both reflexive interviews the first taking place with morning students and the second, with evening students happened in the second semester of 2009. The results showed the existence of dominant metaphors, which were present both in the students drawings and speech. Brazil, like a stone boat, does not have any territorial frontiers, neither with other countries, nor with the Atlantic Ocean, which was not drown outside, but rather inside the limits of the map. The heart metaphor was related do being Brazilian, known to be very friendly people. The students speech shows that, for them, there is more than one typo of Brazilian, those with whom they identify themselves the hard working ones and the others: the alienated people, the corrupt politicians. However, by analyzing the representations in its three dimensions (image, attitude and information) we were able to learn that the students have a very limited repertoire of information about the country. The information they hold is not enough for them to hold a Law major and become committed professionals. Educational policies that enlarge specific academic contents are absolutely needed. It is only by mastering the information that enables such students to create more complex representations that they will be able to identify and reflect about them, in a trend that will benefit their identify consciousness and allow for action and social commitment